Performance of reactive MgO concrete under increased CO2 dissolution - Dung, Nguyen Tien (2020)
The strength gain of reactive MgO cement (RMC) samples depends on carbonation, which is limited by the formation of an initial carbonate layer and the low dissolution of CO2. This study investigates the use of seeds and NaHCO3 (SBC) to extend the surface area for carbonation and increase CO2 dissolution, respectively. The influence of seeds and SBC on the hydration kinetics of RMC was evaluated by isothermal calorimetry and pH measurements. Mechanical performance results were supported by XRD, TG-DTG and SEM, which identified the amount and morphology of final phases. The introduction of well-dispersed seeds within the initial mix design enabled the enhanced nucleation of carbonates, while the dissolution of CO2 was improved by the increased initial pH and HCO3– provided by SBC. The simultaneous use of seeds and SBC led to dense microstructures composed of interconnected carbonate networks, resulting in 142% increase in 28-day strengths (24 vs. 58 MPa).